2021
DOI: 10.4314/tjs.v47i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activities of Tanzanian Moringa oleifera Extracts against Escherichia coli and Klebsiella pneumonia Clinical Isolates

Abstract: In vitro antibacterial activities of methanolic leaf and seed extracts of Moringa oleifera grown in Dodoma, Tanzania were evaluated using standard microdilution and disc diffusion methods against extended spectrum beta lactamase producing Gram negative bacteria (Escherichia coli and Klebsiella pneumoniae). Microdilution method showed no activity at concentration of 20 mg/mL for all the extracts except leaf extract which exhibited minimum inhibition at concentration of  2.5 µg/mL for E. Coli but when high conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition Xiong et al, (2018) investigated the use of MOL as beds to disinfect the raw water from E. coli, which exhibited a high removal efficiency of 99.0 %, with a total coliform count of 3-4 cfu\ 100 ml. In the same line, Chandrashekar et al, (2020); Begum et al, (2021) indicated that a crude extract from Moringa contained a coagulant protein that exhibited cell aggregation and growth inhibition of E. coli and S. paratyphi B coliform bacteria, which was attributed to the presence of peptides with antibacterial properties in the Moringa extract. In a recent study conducted by Semanka et al, (2022), it was observed that reduction of coliform count recorded more than 65 % of the total coliform.…”
Section: Fecal-coliform Antibacterial Susceptibility To Molmentioning
confidence: 95%
“…In addition Xiong et al, (2018) investigated the use of MOL as beds to disinfect the raw water from E. coli, which exhibited a high removal efficiency of 99.0 %, with a total coliform count of 3-4 cfu\ 100 ml. In the same line, Chandrashekar et al, (2020); Begum et al, (2021) indicated that a crude extract from Moringa contained a coagulant protein that exhibited cell aggregation and growth inhibition of E. coli and S. paratyphi B coliform bacteria, which was attributed to the presence of peptides with antibacterial properties in the Moringa extract. In a recent study conducted by Semanka et al, (2022), it was observed that reduction of coliform count recorded more than 65 % of the total coliform.…”
Section: Fecal-coliform Antibacterial Susceptibility To Molmentioning
confidence: 95%